Применение низкоэнергетических ЭМП для управляющего воздействия на биофизические процессы в биологических объектах - Черенков, Александр Данилович; Аврунин, Олег Григорьевич (НТУ "ХПИ", 2014)
В статье рассмотрены информационные процессы в биологических объектах на клеточном уровне и определены основные требования к внешнему электромагнитному излучению для лечения животных.

The article describes the information processes in biological systems at the cellular level and the main requirements for the external electromagnetic radiation for the treatment of animals. The feature of living organisms as biocybernetical systems is their ability to change tactics and strategy of management for better using of favourable conditions for the development and good adaption to unfavourable habitat.
Application EMF of low energy for manipulated biophysical processes in biological objects
Keywords: электромагнитное излучение; лечение животных; информационные процессы; electromagnetic radiation; treatment of animals